Analysis of seized peptide and protein‐based doping agents using four complimentary methods: Liquid chromatography coupled with time of flight mass spectrometry, liquid chromatography–ultraviolet, Bradford, and immunoassays. Issue 7 (14th March 2021) - Høj, Lars Jakobsen; Rasmussen, Brian Schou; Dalsgaard, Petur Weihe; Linnet, Kristian
Abstract: Analysis and identification of seized doping‐related products are important tasks for customs or forensic laboratories in order to prevent potentially dangerous and illegal compounds to go into circulation. At the Section of Forensic Chemistry in Copenhagen, we have a workflow consisting of four complimentary validated methods to identify common doping‐related substances: liquid chromatography‐ultraviolet (LC‐UV), LC coupled with time of flight mass spectrometry (LC‐TOF‐MS), the colorimetric Bradford assay, and an immunoassay. The Bradford assay screens for peptide or proteins in the sample, and the immunoassay confirmed human chorionic gonadotropin (hCG). LC‐UV was carried out with a C4 protein column for identification of peptides and proteins from a standard reference library, based on retention times and ratios between peak areas at 220, 254, and 280 nm. LC‐TOF‐MS was performed using a C18 column, and identification was based on comparison of the retention time and the accurate mass with those of reference standards. In 2019, we received 36 samples for peptide/protein analysis, all of which were tested using the LC‐UV, LC‐TOF‐MS, and colorimetric method, and samples suspected of containing hCG were confirmed with an immunoassay. We found a total of 15 samples containing an illegal doping substance, 12 samples containing substances not prohibited by the Danish Doping List, and nine samples containing no peptides or proteins. In conclusion, the four complimentary methods constitute a suitable approach for identifying common peptide/protein doping substances in the day‐to‐day routine of a forensic laboratory, with limited sample preparation and interpretation of data. Abstract : Four complimentary validated methods were developed and used to identify common doping‐related substances in Danish seizures from 2019.